2015
DOI: 10.1111/pme.12595
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Intradiscal Biacuplasty for Treatment of Discogenic Lower Back Pain: A 12-Month Follow-Up

Abstract: Clinically significant improvements after IDB initially reported at 6 months were maintained at 9 and 12 months. The cross-over subjects had similar improvement in all outcome measures at all observed time points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
(28 reference statements)
1
17
0
Order By: Relevance
“…The majority of publications examining standard RFA (SRFA) for patients with this indication conclude follow‐up at or before 6 months, consistent with the anticipated known effect for SRFA . In addition, twelve‐month analgesia utilizing CRFA has been previously described for painful conditions in the back . Ho et al previously suggested that CRFA can provide analgesic effect for 24 months when used to treat painful sacroiliac joints, and data from this series continues to support that concept …”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The majority of publications examining standard RFA (SRFA) for patients with this indication conclude follow‐up at or before 6 months, consistent with the anticipated known effect for SRFA . In addition, twelve‐month analgesia utilizing CRFA has been previously described for painful conditions in the back . Ho et al previously suggested that CRFA can provide analgesic effect for 24 months when used to treat painful sacroiliac joints, and data from this series continues to support that concept …”
Section: Discussionsupporting
confidence: 65%
“…Cooled radiofrequency ablation (CRFA) has been shown to provide at least 12 months of relief for painful conditions of the spine, and has recently emerged as a minimally invasive option for pain control in patients with OA of the knee . An initial report by Bellini suggested CRFA can provide 12 months of analgesia when used in this patient population .…”
Section: Introductionmentioning
confidence: 99%
“…IDRFT procedures were discussed in 3 of the reviewed trials. Kapural et al [31] found a significant benefit in pain reduction, function, and disability at 6 months in patients with single level discogenic pain who received IDRFB compared with sham [30]. However, in another RCT, Barendse showed no benefit of IDRFT vs. sham.…”
Section: Discussionmentioning
confidence: 94%
“…Additional studies have evaluated the effectiveness of Intradiscal ablative procedures including electrothermal [21][22][23] and radiofrequency thermocoagulation [24 •• , 25 •• , [26][27][28], anuloplasty [29], biacuplasty [30][31][32], and coblation [33] in reducing discogenic LBP. Of these trials, 6 were randomized controlled trials.…”
Section: Ablative Proceduresmentioning
confidence: 99%
“…Significant improvement was observed in physical function, pain, and disability at 6 months when compared with sham treatment . However, this beneficial effect was later lost, as the 12‐month data failed to show a statistically significant difference in outcomes between the two groups .…”
Section: Interventional Options For Diagnosis and Treatment Of Low Bamentioning
confidence: 97%